2021
DOI: 10.1371/journal.pone.0247866
|View full text |Cite
|
Sign up to set email alerts
|

Using machine learning to improve risk prediction in durable left ventricular assist devices

Abstract: Risk models have historically displayed only moderate predictive performance in estimating mortality risk in left ventricular assist device therapy. This study evaluated whether machine learning can improve risk prediction for left ventricular assist devices. Primary durable left ventricular assist devices reported in the Interagency Registry for Mechanically Assisted Circulatory Support between March 1, 2006 and December 31, 2016 were included. The study cohort was randomly divided 3:1 into training and testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…It used CD57 to identify NK cells 25,26 instead of CD56 due to better specificity 60-62 (Extended Data Fig. 1e) and superior prognostic value in HCC 10 . Furthermore, we present the largest cohort of mIHC-stained WSIs that integrates spatial technologies and ML to focus specifically on immune profiles, unlike previous studies that relied on H&E-stained WSIs with ML that are potentially biased towards tumor morphology 17,41,63 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It used CD57 to identify NK cells 25,26 instead of CD56 due to better specificity 60-62 (Extended Data Fig. 1e) and superior prognostic value in HCC 10 . Furthermore, we present the largest cohort of mIHC-stained WSIs that integrates spatial technologies and ML to focus specifically on immune profiles, unlike previous studies that relied on H&E-stained WSIs with ML that are potentially biased towards tumor morphology 17,41,63 .…”
Section: Discussionmentioning
confidence: 99%
“…Through mIHC staining analysis, we determined the percentages of SPON2 + , ZFP36L2 + , ZFP36 + , VIM + , or HLA-DRB1 + cells at IF and TC for use as predictor variables in building machine learning models that are predictive of HCC relapse outcomes. We evaluated a battery of machine learning models, including a generalized linear model 5 , a support vector machine 7 with a linear kernel or a radial kernel, a decision tree model 8 , a random forest model 9 , and an extreme gradient boosting model 10 .…”
Section: Developing a Tumor Immune Microenvironment Score (Times) Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The joint PET evaluation improves had a good performance (AUROC = 86%), and the SVM algorithm outperformed the other methods evaluated. In a study [ 30 ], including a total of 16,120 patients, ML improved one-year risk discrimination in predicting durable left ventricular assist devices as compared to logistic regression (C-index 71% vs. 69%, P < 0.001); however, calibration metrics were comparable. Globally, these studies confirm limited value of current clinical models to accurately predict the presence of myocardial ischemia at stress MPI [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kilic et al revealed that there is an increase in the use of durable left ventricular assist devices (LVAD) being implanted in the United States but there was no widely used risk stratification tool for LVAD therapy. By utilizing the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) database they studied the 90-day and 1-year mortality rates following primary LVAD implantation using both logistic regression and machine learning approaches and found that machine learning models were both well-calibrated and had improved discriminatory capability as compared to logistic regression [ 29 ]. Wang et al developed and validated a machine learning method that can predict the amount of red blood cell transfusions required for a cardiothoracic surgery and showed excellent results [ 30 ].…”
Section: Role Of Ai In Preoperative Performance and Safety In Cardiot...mentioning
confidence: 99%